Quantitative audit of the content of histopathology reports. - Campbell, F (1994)
An audit of histopathology reports presents the problem that the output is textual and difficult to quantify. This makes the definition of an adequate report subjective and susceptible to observer variation. A procedure has been developed which allows the quantitative analysis of reports and facilitates the development of local reporting guidelines. A topic is selected; the auditor then lists the possible details that may be included in the report and notes how many reports from a sample include each detail. The results are discussed at a departmental meeting with the aim of agreeing on reporting guidelines. At a later date another sample of reports can be analysed for compliance with the guidelines and compared with the previous reports. Problems with compliance can be discussed further and at the audit meeting the guidelines may be amended appropriately, thus completing the audit cycle. This method of audit has the advantage that the results are quantitative and that the group discussion and re-examination of the guidelines has educational value.